Volatility and Transmission of Coffee Prices in Indonesia - Sukiyono, Ketut; Dita, Putri Tiara; Romdhon, Muhammad Mustopa (Jurnal Social Economic of Agriculture, 2025)
Commodity prices, including prices for agricultural products, play a very important function in making decisions both in production and marketing. Therefore, the study of price volatility and transmission is very important to be carried out to obtain price behavior in the market, including coffee prices. This research is aimed at analyzing the volatility and transmission of Indonesian coffee prices at the producer, the national (f.o.b price), and the International level. The data used are monthly data of coffee beans at producer level in Bengkulu province, Indonesia f.o.b prices, and International coffee prices in 2010:1 "“ 2017:12. The ARCH-GARCH method is used to analyze the coffee price volatility, while the ECM method is used for coffee price transmission analysis. The research shows that producer-level coffee prices in Bengkulu Province and International experienced a low price volatility. The transmission of coffee prices from international prices to f.o.b Indonesia price experienced a price adjustment of 13.07% towards the price balance. Meanwhile, the coffee price transmission from International prices to prices at the producer level in Bengkulu Province experienced a price adjustment of 8.93% towards the price balance.